Correlation of RDW and Severity of Community Acquired Pneumonia in Children Aged Between 6 Months to 5 Years - Fatima, Zeeshina; Sami Ullah; Sami, Hafiz Ahmad (Indus Journal of Bioscience Research, 2025)
Background: Community-acquired pneumonia (CAP) is a leading cause of morbidity and mortality among children under five in developing countries. Red cell distribution width (RDW) has emerged as a potential inflammatory biomarker in a variety of diseases, but its relationship with CAP severity in children is poorly understood. Objective: To determine the relationship between RDW levels and the severity of community-acquired pneumonia in children aged 6 months to 5 years who presented to DHQ Hospital, Gujranwala. Methods: This prospective observational study included 280 children diagnosed with CAP between June and December 2024. Chronic hematological, liver, or kidney diseases were excluded. CAP severity was determined using World Health Organization (WHO) criteria. Complete blood counts were obtained upon admission. The primary result was a correlation between RDW and severity scores. Secondary outcomes included hospitalization, ICU admission, and death. Results: Of the 280 children, 220 were followed up. Out of 220, 110 (50%) had mild, 78 (35.5%) moderate, and 32 (14.5%) severe CAP. The mean RDW increased with severity: mild (13.2 ± 0.8%), moderate (14.1 ± 1.0%), and severe (15.6 ± 1.1%) (p